Have advances in surgical implants and techniques in hemiarthroplasty for intracapsular hip fractures improved patient outcomes compared to THA? A systematic review and meta-analysis of the evidence. Issue 6 (December 2022) - Wek, Caesar; Reichert, Ines; Gee, Matt; Foley, Rob; Ahluwalia, Raju
Abstract: Introduction: Hip fractures are common orthopaedic hospital admissions and result in considerable morbidity and mortality in the patients affected. The aim of this study is to review how advances in surgical implants and techniques have impacted on outcomes of Hemiarthroplasty (HA) vs Total Hip Arthroplasty (THA) for displaced intracapsular neck of femur fractures. Methods: A systematic review and meta-analysis of randomised controlled trials was performed and reported in accordance with the Preferred Reporting Items for Systematic Reviews & Meta-analyses (PRISMA) statement. We included all studies that were prospective randomised controlled trials comparing the outcomes THA versus HA in patients with displaced intracapsular neck of femur fractures. Results: 13 randomised controlled trial met the eligibility criteria; the overall pooled sample size was 3050 patients. The evidence suggests that the short-term functional outcomes favour THA, without strong evidence of a clinically significant benefit. More recent larger RCTs suggest limited functional improvement conferred by THA vs. HA, whilst the risks of complications may outweigh these small gains. Overall, THA is associated with higher dislocation rates without a significant need for re-operation, but no increase in infection or need for transfusion over HA. Consultant or equivalent supervision has a positive effect on outcomes in both groups. Conclusion: The literature supports a change in direction, this meta-analysis confirms HA surgery has equivalent clinical outcomes and possibly a lower mortality in octogenarians and provides further evidence for the stratification of THA treatment in displaced intracapsular neck of femur fractures is urgently required. Level of evidence: 1. Highlights: There is an increase in mortality in patients >80 who undergo THA instead of HA. We found no difference in re-operation and mortality between THA vs HA. The outcome scores were higher for THA, but this may not be clinically significant. Dislocation rates were higher in the THA group with a 20% RR in patients >80. Implants affect outcome and like THA, HA prostheses should be recorded in the NJR.